Numerical Evaluation of the Adverse Effects of Economic Instability on Consumer Buying Behaviour in Nigeria - Duruojinkeya, Prisca Udodiri; Ishola, Christie Yemisi; Chibuisi, Chigozie; Osu, Bright Okore (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
The buying behaviour in consumer research encompasses the decision-making processes customers undergo when purchasing goods and services. The buying behaviour of consumers under economic instability is influenced by economic instabilities such as hyperinflation, unstable dollar to naira exchange rate, removal of fuel subsidy without predictive feasibility study analysis, increment of value added tax (VAT) and high electricity tariff. These economic instabilities result to volatility adverse effects of devaluation of naira, income fluctuations, disruption of financial planning and reduction of household expenditure, increased cost of imported raw materials leading to an increase in production and marketing costs. Amid these economic instabilities, there is urgent need to evaluate its volatility adverse effects on consumers’ buying behaviour and this can be modeled as Econometric Instability Time-Delay Differential Equation (EITDDE). Numerically, this study aims to evaluate and proffer best ways to overcome the volatility adverse effects of economic instability on consumers’ buying behaviour in Nigeria. Some examples of the modeled equation were solved using Extended Block Adams Moulton Methods (EBAMM) with the use of modeled mathematical sequences for evaluation of the instability delay and noise terms. The instability delay and noise terms were evaluated by applying acceptable ideas of developed sequences. The discrete schemes of the applied numerical method were obtained through the use of linear multistep collocation procedure using matrix inversion approach. Following the volatility display of the numerical results of the method which represents the volatility adverse effects of five dimensions of economic instability on consumers’ buying behaviour, the Absolute Instability Errors (AIEs) of partition number of EBAMM produced better and faster numerical results than the partition numbers and 2 by giving the Least Minimum Absolute Instability Errors (LMAIEs) at a Lower Computational Time (LCT) when compared with established methods. This study recommends that the Nigerian government should adopt more robust and consistent monetary policies and diversify its economy by investing in non-oil sectors such as agriculture, technology, and manufacturing in order to create a more stable and resilient economic environment and to improve consumers’ buying behaviour.